Rapid, High-Level Transient Expression of Papillomavirus-Like Particles in Insect Cells. (May 1996) - Benincasa, Diana; Silberklang, Melvin; Mark, George E.; Ludmerer, Steven W.
Empirical scanning of natural or engineered peptide sequences for functional residues is inherently dependent upon efficient expression of large numbers of individual sequence variants to assay their relative functional potency. The insect baculovirus system has been widely used for expression of viral coat proteins, but it generally requires prior isolation and expansion of a plaque-purified recombinant viral stock to generate useful quantities of selfassembled virus-like particles. In search of a more rapid means of expression of analytical levels of the L1 coat protein of cottontail rabbit and human type 11 papillomaviruses, we found that even brief transient cotransfection of insect cells with baculovirus plasmid transfer vectors and viral DNA yielded assembled particles that were immunologically indistinguishable from particles obtained with plaque-purified viral stocks. Within six days of plasmid/viral DNA cotransfection of Sf9 cells, at least 1–2 mg of assembled L1 particles/100-mm plate could be demonstrated, which proved more than sufficient to assay functionality. Transient cotransfection of insect cells should provide general utility for rapid high-level expression of sets of protein sequence variants, as well as other sequencescanning applications such as sequence optimization in protein engineering.